Fintech, bank funding, and economic growth in Sub-Saharan Africa - Tafirei Mashamba; Shenaaz Gani (Cogent Economics & Finance, 2023)
The emergence of financial technology (Fintech) has greatly impacted the financial landscape in Sub-Saharan Africa (SSA) in recent years. The impact on bank funding and economic growth in the region cannot be ignored. This paper examines the extent to which Fintech has affected bank funding and economic growth in the region by utilizing data from 56 banks across 19 SSA economies between 2010 and 2020. The analysis was conducted using a covariance-based structural equation modeling method. The results show that Fintech disruptions have triggered an increase in equity funding for banks, while having negligible effects on deposit and long-term debt financing. The study also outlines that Fintech's limited size within the financial system has ultimately restricted its effects on economic growth in SSA. Furthermore, the study did not find evidence of Fintech mediating the impact on economic growth via the bank funding channel, suggesting that SSA banking systems are capable of resisting Fintech disruptions for financial stability. Overall, these findings highlight the resilience of bank funding structures to Fintech disruptions, emphasizing the importance of prudent funding management and continued investment in Fintech for sustained economic growth in Sub-Saharan Africa. However, as Fintech continues to evolve and grow, policymakers should remain vigilant and monitor its impact on the financial system and economic growth in the region. By understanding the implications of Fintech on bank funding and economic growth in SSA, this paper contributes to the ongoing discussion on the potential benefits and challenges of technological innovations in the financial sector.
Keywords: C3; G1; O1; O4; 330; bank funding; economic growth; Fintech; structural equation modeling; Sub-Saharan Africa